Do Recruiters Select Workers with Different Personality Traits for Different Tasks? A Discrete Choice Experiment - Caroline Wehner; Andries de Grip; Harald Pfeifer (Institute of Labor Economics (IZA), 2020)
This paper explores whether firms recruit workers with different personality traits for different tasks. For our analysis, we used data from a discrete choice experiment conducted among recruiters of 634 firms in Germany. Recruiters were asked to choose between job applicants who differed in seven aspects: professional competence, the 'big five' personality traits and the prospective wage level. We found that all personality traits affect the hiring probability of the job applicant; among them, conscientiousness and agreeableness have the strongest effects. However, recruiters' preferences differed for different job tasks. For analytical tasks, recruiters prefer more open and conscientious applicants, whereas they favour more open, extraverted, and agreeable workers for interactive tasks.
Keywords: J23; D91; M51; 330; recruitment; personality traits; tasks; discrete choice experiment